Chance Encounters. Issue 1 (2nd January 2018) - Ruccio, David F.
Abstract : This essay focuses on two aspects of the author's encounters with Stephen Resnick over the years: his teaching and his writings. It explains why he was such a successful teacher and how he developed such an original research project in rethinking the Marxian critique of political economy.